Repeated pulmonary embolism with cardiac arrest after uterine artery embolization for uterine arteriovenous malformation: A case report and literature review - Balkenze Imankulova (Taiwanese Journal of Obstetrics & Gynecology, 2018)
Objective: Uterine arteriovenous malformation (AVM) is an abnormal and nonfunctional communication between uterine arteries and veins, currently managed by uterine artery embolization (UAE). Pulmonary embolism (PE) is the most severe and life-threatening complication of this procedure. Case report: We report a case of 27 year-old woman with heavy vaginal bleeding and abdominal pain caused by AVM. UAE was performed uneventfully, but 2 h after the procedure the first attack of pulmonary embolism occurred, treated by anticoagulation therapy. Second attack happened on the third postinterventional day. Considering vaginal bleeding, continued extracorporeal membrane oxygenation (ECMO), and suspicion of embolic particles arising from uterus, a subtotal hysterectomy was done. Patient was discharged two weeks following surgery, after complete recovery. Conclusion: Although AVM is managed by UAE, clinicians must be aware of complications. To avoid PE, we suggest only large sized microspheres for carefully selected patients. Keywords: Uterine artery embolization, Uterine arteriovenous malformation, Pulmonary embolism